Laju Percepatan Perkembangan Perbankan Syariah Melalui Penerapan Tata Kelola Syariah - Rachmad Nor Firman (JOURNAL OF SHARIA ECONOMICS, 2019)
Indonesian sharia banking industry’s growth chart shows a rising, albeit decelerating. Islamic banking accounted for 4.81% of market share to achievethe growth assets 11.97% as of June 2018. At the global level, the Islamic financial services sector including banking, control of 3% and together with Qatar, Saudi Arabia, Malaysia, United Arab Emirates and Turkey the driving force of Islamic finance in the future. One of the strategic issues that are a barrier is a public misperception of the Islamic banking, either on contract, products and services that are considered not compliant with Islamic principles. Implementation of governance is an effort to accelerate the growth of Islamic banking. Keywords: Islamic Banking, Governance, Acceleration of Growth